ANALISIS PENAMPANG KOLOM BETON BERTULANG PERSEGI PANJANG BERLUBANG - Marzon Marzon; Mukhlis Islam; Elhusna Elhusna (Inersia: Jurnal Teknik Sipil, 2019)
Installation of pipes (conduit) in the building columns often found in reinforced concrete structures. The installation of pipes inside the columns is utilized as sanitary and mechanical electrical pipes. The case research in this study is to analyze the rectangular column with the applied research type (applied/pratical research). This research aims to analyze the impact of the holes on square rectangular columns. This calculation consists of 675 samples with differentconcrete compression strength (f'c), reinforcement area, holes area, and the dimensions of the column. Analysis of the calculation of hollow rectangular columns using the stress-strain relationship equation developed by Hognestaad. The results of the analysis on hollow rectangular columns resulted in a decrease column capacity. The largest decrease of the rectangular column capacity occurred on holes area of 7%, with concrete compression strength 30 MPa, and dimensions of the column 450 x 1800 mm which is 16.97%.